QUALITY OF LIFE IN PATIENTS WHO HAVE UNDERGONE REVERSE SHOULDER ARTHROPLASTY - Leite, Luiz Marcelo Bastos (Acta Ortop Bras, 2019)
OBJECTIVE: To evaluate the health-related quality of life (HRQoL) of patients who have undergone reverse shoulder arthroplasty (RSA) for rotator cuff arthropathy (RCA). METHODS: A retrospective study with 35 patients who underwent RSA from August 2007 to July 2015. We collected clinical data and applied the 36-item Short Form Health Survey (SF-36). RESULTS: Of the 35 patients, 29 (82.9%) were female, and mean age was 75.71 years, ranging from 50 to 89 years. The dominant side was frequently affected (68.6%), and most of the cases were Hamada type 3 (57.1%). The Mackenzie approach was used in 30 patients (85.7%). Physical and mental HRQoL was not associated with severity of RCA before RSA. Lower scores for Physical Functioning, Role Physical, Bodily Pain, and Physical Component Summary (PCS) were associated with other orthopedic comorbidities. Vitality, Role Emotional, Mental Health, and Mental Component Summary (MCS) were significantly higher in patients without depression. Orthopedic comorbidity and depression predicted lower PCS and longer follow-up time predicted better PCS scores. Depression was also a predictor of the MCS. CONCLUSION: Patients who had undergone RSA for RCA had good HRQoL. Longer follow-up time was associated with better HRQoL. Good results were maintained over the follow-up period. Level of evidence II, retrospective study.